CHARACTERISTICS OF SEEDS AND GROWTH INDICATORS OF DOUGLAS FIR SEEDLINGS OF DIFFERENT GEOGRAPHICAL ORIGIN - Fuchylo, Ya. D.; Los, S. A.; Sbytna, M. V.; Plotnikova, O. V. (Forestry and Forest Melioration, 2018)
Introduction Douglas fir (Pseudotsuga Menziesi (Mirb.) Franco) is known as one of the largest conifers in the world. Douglas fir had been brought into Ukraine more than 100 years ago (Gunchak, 1998). The results of evaluation of its adaptation and productivity in different climates conditions of Ukraine are quite successful (Elwes, 1906; Gunchak, 1998, Los, 2008; Debrynyuk, 2013). On the other hand, the seed’s origin of most Douglas fir stands in Ukraine is unknown and it is not still possible to identify the most available locations in natural areas for seed collection for cultivation in Ukraine. For the solution of the problem, the provenance trials were created from seeds collected in natural habitats of the species. Preliminary results from the studies of seeds and seedlings of Douglas fir of different geographical origins are represented in our papers (Khmilevsky, 1987; Los, 2016; Sbytna, 2016). The aim of this study is a synthesis of research results of seed characteristics and growth properties of 2-year-old Douglas fir seedlings of different geographical origin in the central and north-eastern part of Ukraine. Materials and Methods Douglas fir seeds were received in summer 2012 from the USA. The seedlings were grown in Boyarka Forest Research Station (Kyiv region), Kharkiv Forest Research Station and Huty Forest Economy for two years. As a control, seeds collected in the clonal seed orchard of Kolomyia Forest Enterprise (K-1) and in forest trial plantations of Kharkiv Forest Research Station (K-2) were used. The size, color, and mass of the seeds and the seedling size were determined. Results and Discussion The seeds of different origin were insignificantly differed by the color – from brown to dark brown. The seeds harvested in British Columbia and on highlands of Arizona and New Mexico have a smaller size, and ones from the Pacific Northwest have a bigger size, besides regardless of the altitude. The positive moderate correlation was detected between the average annual temperature in the region of seed harvesting and the average seed length (r = 0.53). Among the samples from the USA, the seeds from Washington had the lowest weight of 1,000 seeds (10.5 g) and the seeds from New Mexico and Arizona had the largest weight (13.2 g). The weight of 1,000 seeds harvested in the trial plantations in Kharkiv Forest Research Station exceeded this index and was 13.7 g. A strong and moderate correlation of seed weight and geographical location of parent stands (r = -0.80 for latitude and r = 0.75 for longitude), altitude (r = 0.75) and rainfall during the growing season (r = -0.54) was found. In Kyiv region, the seedlings grown from seeds harvested in Ukraine (namely, the clonal seed orchard in Kolomyia forest enterprise (K-1) and trial plantations in Kharkiv Forest Research Station (K-2)) had the greatest height and length of a root system. In particular, values of K-1 seedlings height were significantly higher than those of all variants, including the seedlings grown from the seeds of forest trials (K-2). In most cases, variants of American and Canadian origin were far below the K-1. Correlation analysis showed a positive relationship between growth rates of provenances in Boyarka Forest Research Station and the latitude and longitude of parent stand locations in which the seeds had been harvested (r = 0.34–0.81). Less quantity of variants grown in Kharkiv region and, therefore, less difference of parent stands conditions did not allow revealing clear correlation dependence. The indexes of variants from Washington were noted as some better than of variants from New Mexico and Arizona. Correlation analysis showed the tendency for the progenies of parent stands of northern origin to better grow in north-east of Ukraine. Conclusions Samples of different geographical origin differed slightly by color and size. The positive moderate correlation was detected between the average annual temperature in the region of seed harvesting and the average seed length (r = 0.53). The seeds harvested in British Columbia had the shortest length. The seeds from the Pacific Northwest were distinguished by the bigger sizes, besides regardless of the altitude. Samples of different geographical origin differed significantly from each other by seeds weight. The seeds harvested in Washington had the lowest weight of 1,000 seeds (10.5 g), seeds from New Mexico and Arizona had the largest weight (13.2 g). The influence of geographical location of parent stands (r= -0.80 for latitude and r = 0.75 for longitude), altitude (r = 0.75) and rainfall during the growing season (r = -0.54) on the seed weight was found. Sizes of seedlings grown in Kyiv and Kharkiv regions were different. The positive relationship was revealed between growth rates of progenies in Boyarka Forest Research Station and parent stand locations latitude and longitude, in which the seeds were harvested (r = 0.34–0.81). According to preliminary data, the progenies from north-western areas of the USA and Canada had the best growth indexes in the central part of Ukraine; in the northeast of Ukraine, the progenies from Washington and New Mexico did. The Douglas fir from Lincoln and Gila National Forests had the best growth in Kharkiv region. Acknowledgement We thank Dr. Mykola Vedmid, Dr. Sergiy Zibtsev, and Dr. Yu. Bigun for the assistance in seed obtaining. Special thanks for the Dr. Brad St. Clair, Research geneticist, US Forest Service, Pacific Northwest Research Station for organizing the seed harvesting.